ANALISIS PERANCANGAN DATABASE MANAGEMEN SISTEM UNTUK SISTEM PENUNJANG PROSES BISNIS WEDANG UWUH INSTAN - Titik Rahmawati; Eka Yulia Sari; Anjasmara Tanjung Shakti; Atthaya Nanda Yomura (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2023)
The use of information technology can support business people in supporting their business processes. Wedang uwuh instan which is a form of creativity for Industrial Engineering students at the Universitas Sarjanawiyata Tamansiswa that managed by PT Sruput Jaya which is a socially and profit-oriented student business unit. The current marketing reach is still offline and in the surrounding environment. The target consumer has not been given the maximum information platform regarding Wedhang Uwuh Instan products so consumer interest is lacking. Therefore it is necessary to make an application to support business processes at PT Sruput Jaya as a portal for online marketing and ordering. The development of such system technology cannot be separated from the development of a database that is used as a place for managing and using data in a running information system. Database development can be done using the DBSDLC (Database System Development Lifecycle) method. There are 3 processes in database design using the DBSDLC method, namely Conceptual Schema Design, Logical Design, and Physical Design. The results of this study are in the form of a business process support system design model at PT Sruput Jaya in the form of marketing applications and instant wedang uwuh online ordering. This model will support further system development.